Production and GC-MS Analysis of Biodiesel from Waste Cooking Oils using Oleaginous Yeast - KARTHIKA.S; KANNAHI.M (International Journal of Pharma and Bio Sciences, 2018)
The present study was carried out to produce and analyze biodiesel from waste cooking oils using fungal lipids produced by the isolated organisms. Soil sample was collected from paddy field, Thiruthuraipoondi Taluk, Thiruvarur District, Tamil Nadu, India. The physico-chemical properties of the soil samples were analyzed. The soil sample was subjected to serial dilution agar plating method for the isolation and identification of yeast Saccharomyces cerevisiae, Saccharomyces kudriavzevii and Saccharomyces paradoxus confirmed according to standard manuals. The yeast cell biomass, lipid estimation and biodiesel production was analyzed. Fatty acid composition of biodiesel was determined by GC-MS. The maximum biodiesel production was observed in Saccharomyces kudriavzevii and it was mediated transesterification process. The advantages of utilizing biodiesel replacing conventional fuel are that biodiesel in engines are non-toxic, biodegradable, renewable and less pollutant in emissions. Engine life can be prolonged by reducing the frequency of engine part replacement and by increasing the lubricity. Due to the high cost of feedstock used for biodiesel synthesis, it is not yet commercialized globally. Commercial utilization of biodiesel will lead to many advantages like green cover for waste land, greater support for agriculture and rural economies, and thereby reduce dependence on imported crude oil and a smaller rate of increase in air pollution. The study also concludes that the oleaginous yeast is the best source of biodiesel producer and can be used for future research programs. We can further focus on the genetic and metabolic engineering aspects which are likely to have the greatest impact on improving the economic production of yeast biodiesel.